Clinical Psychology and Congenital Heart Disease Lifelong Psychological Aspects and Interventions - Callus, Edward; Quadri, Emilia; SpringerLink (Online service) (Milano : Springer Milan : Imprint: Springer, 2015)
This book describes those psychological features specifically characteristic of patients with congenital heart disease, from birth to adulthood. The combination of case studies, descriptions of life experiences and psychological recommendations and collaboration with non-profit organizations in the field ensure that it will serve as an excellent day-to-day learning tool. Technological advances in cardiology and cardiac surgery have resulted in an increase in the number of adults with congenital heart disease, creating a new emergency. From when they are born, these patients and their relatives require extensive support for many reasons, including the uncertainty and restrictions in their lives, frequent hospitalizations and difficulties in the work and social spheres. Clinical Psychology and Congenital Heart Disease explains how psychology can contribute to healthcare treatment of patients with congenital heart disease and their families. Emphasis is placed on the need for a multidisciplinary approach to ensure the well-being of the patient and the clinician is provided with insights and instruments that will assist greatly in the provision of appropriate support.
PART I CHD AND HUMANIZATION OF HEALTH CARE Congenital heart disease: medical overview -- Humanisation of health care context.- PART II FAMILY DYNAMICS, PSYCHOLOGICAL ASPECTS AND NEUROPSYCHOLOGICAL FUNCTIONING IN CHILDREN AND ADOLESCENTS WITH ConHD Adjusting to congenital heart disease in adolescence: the role of patients' personality and self -- Psychological aspects in children and adolescents with ConHD -- Neuropsychological aspects in children and adolescents with ConHD -- PART III PERSONALITY DEVELOPMENT, PSYCHOLOGICAL FUNCTIONING, QOL AND TREATMENT PREFERENCES IN ADULTS WITH ConHD Psychological functioning in adults with congenital heart disease -- Quality of life in ConHD -- End of life care and treatment preferences -- PART IV PSYCHOLOGICAL AND PEER TO PEER INTERVENTIONS AND THE IMPORTANCE OF NON PROFIT ASSOCIATIONS Psycho-cardiology and the role of the psychologist in acquired and congenital heart disease -- Medical Art Therapy for patients with congenital heart disease -- Communication and relational issues of the relationship between health care professionals and patients with ConHD -- The importance of associations and peer to peer support -- Peer counselling in congenital heart disease.
Keywords: Psychology; Cardiology; Psychology, general; Cardiology